2006
DOI: 10.1051/rnd:2006016
|View full text |Cite
|
Sign up to set email alerts
|

A review of the effects of supplementary nutrition in the ewe on the concentrations of reproductive and metabolic hormones and the mechanisms that regulate folliculogenesis and ovulation rate

Abstract: -This paper discusses the phenomenon of nutritional flushing in ewes whereby increased nutrition stimulates folliculogenesis and ovulation rate. In addition the paper reviews recent findings on the effects of increased levels of nutrition on the blood concentrations of reproductive and metabolic hormones in the ewe and some of the intraovarian changes that take place in response to nutritional stimulation. Finally, in the paper, we propose a model of the physiological mechanism for the nutritional stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
223
2
22

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(278 citation statements)
references
References 40 publications
11
223
2
22
Order By: Relevance
“…This was the same for twins (p<0.05). The current results regarding kid growth emphasised the importance of additional feeding before mating and during lactation in extensive goat farming (Martin et al 2004;Scaramuzzi et al 2006;Sultana et al 2012). It has been reported that the nutritional level in maternal feeding during pregnancy affected the number of secondary muscle fibres in striated muscle tissue in foetus which had an effect on birth weight (Dwyer et al 1994;Tygesen & Harrison 2005;Tygesen et al 2007).…”
Section: Resultsmentioning
confidence: 81%
“…This was the same for twins (p<0.05). The current results regarding kid growth emphasised the importance of additional feeding before mating and during lactation in extensive goat farming (Martin et al 2004;Scaramuzzi et al 2006;Sultana et al 2012). It has been reported that the nutritional level in maternal feeding during pregnancy affected the number of secondary muscle fibres in striated muscle tissue in foetus which had an effect on birth weight (Dwyer et al 1994;Tygesen & Harrison 2005;Tygesen et al 2007).…”
Section: Resultsmentioning
confidence: 81%
“…This suggests that there are nutritional inputs, perhaps some form of 'nutrient sensing or signalling' that are not associated with whole body energy status but can nevertheless stimulate the hypothalamic-pituitary-gonadal axis. At gonadal level, the ovarian follicles of sheep respond strongly to direct inputs from glucose, fatty acids and a number of metabolic hormones, and there are local intra-follicular nutrient sensing and integrative pathways and mechanisms that modulate gonadotrophin-stimulated folliculogenesis and regulate ovulation rate (review: Scaramuzzi et al, 2006). This concept has not been tested for the testis of the sheep.…”
Section: Dimension 3 -The Communication Dimensionmentioning
confidence: 99%
“…The breeding season is stimulated by a reduction in the hours of daylight (negative photoperiod), with the largest percentage of conceptions occurring in autumn and winter. Conception within autumn and winter results in kidding during spring, when feed supply and environmental conditions are usually most favourable (Scaramuzzi et al, 2006;Fatet et al, 2011).…”
Section: Introductionmentioning
confidence: 99%